2022
DOI: 10.1177/02601060221127853
|View full text |Cite
|
Sign up to set email alerts
|

The effects of consuming a Mediterranean style diet on associated COVID-19 severity biomarkers in obese/overweight adults: A systematic review

Abstract: Background COVID-19 severity is strongly associated with high Body Mass Index (BMI) (≥25kg/m2) amongst adults and elevated inflammatory markers have enabled prediction of disease progression. The composition of a Mediterranean diet provides favourable outcomes on weight reduction and inflammatory markers. Aim This systematic review aimed to investigate the effects of consuming a Mediterranean diet on BMI and inflammatory markers of obese/overweight adults (≥18 years) at risk of developing severe COVID-19 outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…MedDiet also showed a correlation with inflammation in Dos Reis Padilha’s report [ 75 ], but only in cross-sectional studies. Instead, decreases in BMI, TNF-α, IL-6, and CRP, most of them significant, were reported in the reports by Moore [ 19 ] on the population with overweight or obesity. Analysis of randomized, prospective studies by Genel [ 57 ] showed that a low-inflammatory diet such as MedDiet is associated with greater weight loss, greater decreases in inflammatory biomarkers, greater improvement in measures of pain, and greater improvement in measures of physical function than the usual diet.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…MedDiet also showed a correlation with inflammation in Dos Reis Padilha’s report [ 75 ], but only in cross-sectional studies. Instead, decreases in BMI, TNF-α, IL-6, and CRP, most of them significant, were reported in the reports by Moore [ 19 ] on the population with overweight or obesity. Analysis of randomized, prospective studies by Genel [ 57 ] showed that a low-inflammatory diet such as MedDiet is associated with greater weight loss, greater decreases in inflammatory biomarkers, greater improvement in measures of pain, and greater improvement in measures of physical function than the usual diet.…”
Section: Resultsmentioning
confidence: 96%
“…The Mediterranean diet appeared to be more strongly protective for Alzheimer's Disease than for all-cause dementia. A small improvement in cognitive function in response to a Mediterranean style diet was found No Moore E et al [ 19 ] 2022 6 RCT PubMed Cochrane Library MEDLINE Body Mass Index TNF-α Interleukin-6 NR The main findings indicate a hypocaloric, fiber dense MedDiet to be a short-term (< 4 months) mitigation strategy to significantly reduce BMI and inflammatory markers amongst overweight/obese adults. Results demonstrate that TNF-α, have been significantly reduced over a 3–4-month MedDiet intervention for overweight/obese adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant finding was that the adoption of a Traditional Mediterranean Diet contributed towards to the improvement of patients with recurring colds and frequent inflammatory complications, with significantly reduced episodes and symptoms [27]. A previous systematic review found that Mediterranean diet was reported to lower inflammatory biomarker levels in obese/overweight adults [28]. Similarly, a precedent meta-analysis reported Mediterranean diet adherence effectively reduce SARS-CoV-2 infection by 78% (95% CI 69%–88%), although the authors recommended cautious interpretation due to the paucity of the included studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were divided into tertile groups based on their MDS. inflammatory biomarker levels in obese/overweight adults [28]. Similarly, a precedent meta-analysis reported Mediterranean diet adherence effectively reduce SARS-CoV-2 infection by 78% (95% CI 69%-88%), although the authors recommended cautious interpretation due to the paucity of the included studies [29].…”
Section: Zargarzade H N 2022 [25]mentioning
confidence: 99%